ANALISIS PENDAPATAN USAHA TERNAK AYAM RAS PETELUR DI KOTA PALANGKA RAYA (Studi Kasus: Peternakan Rajawali Poultry Shop dan Satwa Mandiri Farm) - Dicky Porwanto; H. Ahmad Zaki Yamani; Emmy U. Antang (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
This study aims to analyze the income received by breeders in conducting laying chicken breeding for one period of maintenance and analyzing the R/C ratio of laying chicken in one period of maintenance. This research was carried out in the Rajawali Poultry Shop and Satwa Mandiri Farm in the city of Palangka Raya. The research method is Purposive sampling method with the reason that the laying chicken breeding business has a sufficient scale of business and has more livestock populations. Based on the results of the research on the Rajawali Poultry Shop laying hens, it is known that the income of the Rajawali Poultry Shop laying hens is Rp. 1,378,263,000 in one maintenance period with a total of 20,440 chickens raised and the results of the calculation of the level of business efficiency R/C ratio of 1.13 then the livestock breeding of Rajawali Poultry Shop is suitable to run. As for the chicken farms of the Mandiri Farm animal laying race, based on the results of the study, it can be seen that the income of the Livestock Mandiri Farm laying hens is Rp. 2,998,411,000 in one maintenance period with a total of 31,010 chickens raised and based on the calculation of the efficiency level of the R/C ratio of 1.17, the livestock breeding of Satwa Mandiri Farm is feasible to run.